Development of yellow allamanda stem cuttings under different indolebutyric acid concentrations - Pereira, Guilherme Henrique Almeida; Coutinho, Fernando Silva; Costa e Silva, Renata Aparecida; Loss, Arcângelo (Comunicata Scientiae, 2012)
The use of synthetic auxin as a stimulator of rooting in cuttings of Allamanda cathartica can provide increased of roots to development of marketable seedlings. The aim of this study was to evaluate the effect of three concentrations of indolbuthyric acid (IBA) on the development of callus tissue, rooting and sprouting in different stem cuttings from Allamanda cathartica. October 2008, cuttings were collected, immersed in fungicide Captan, treated with IBA and then planted in 45 days in randomized blocks. Every two weeks, we evaluated the percentage of occurrence of calluses, roots and shoots. Independent of IBA concentration, the woody and semi-woody showed the highest percentages of callus, root and sprout. It was found that, in the vegetative propagation of cuttings herbaceous, the application of IBA at 2000 ppm has great influence on development. For semi-woody, is not necessary for the application of IBA. The application of IBA at 250 ppm is sufficient to provide satisfactory development of callus tissue, rooting and shoots in cuttings woody, grown for a minimum period of 30 or 45 days.